Awareness, treatment and control of hypertension in Nepal: findings from the Dhulikhel Heart Study. Issue 1 (4th January 2017) - Karmacharya, Biraj M; Koju, Rajendra P; LoGerfo, James P; Chan, Kwun Chuen Gary; Mokdad, Ali H; Shrestha, Archana; Sotoodehnia, Nona; Fitzpatrick, Annette L
Abstract : Objectives: Although previous studies have suggested alarming rise in the prevalence of hypertension in Nepal, there is dearth of information on its awareness, treatment and control. In this cross-sectional study, we assessed awareness, treatment and control of hypertension among 298 hypertensive adults from the suburban town of Dhulikhel, Nepal. Methods: This cross-sectional study is based on Dhulikhel Heart Study, which included 1073 adults, aged ≥18 years, recruited from randomly selected households. Comprehensive health interviews and blood pressure measurements were completed during home interviews. Hypertensives (systolic blood pressure ≥140 mm Hg or diastolic blood pressure ≥90 mm Hg or receiving antihypertensive medication) were further evaluated for awareness, treatment and control of hypertension. Multivariate regression model quantified the association of the sociodemographic characteristics and the cardiovascular disease (CVD) risk factors with hypertension awareness. Differences between sociodemographic characteristics and CVD risk factors with treatment and control of hypertension were tested using χ 2 tests. Results: A total of 43.6% of all hypertensives (n=298) were aware of their hypertension status. In multivariate analyses, hypertension awareness was associated with increasing age (p<0.001). More than three-fourth (76.1%) of those who were aware of their hypertension status (n=130) were currently on treatment. There were significant differences in treatment status by sex, occupation, age, income quartiles and body mass index. Only 35.3% of those on treatment (n=99) had blood pressure control. Conclusions: The levels of awareness, treatment and control of hypertension in this sample of Nepalese adults were low.